(untitled) (Global Journal of Science Frontier Research, 2018)
The agricultural significance of Potassium (K) has been comprehensively documented owing to its role in plant development and growth. The reserves of K in soil are not available to plant roots for uptake as 98% of the total soil K is mineral bound. The K bearing 2:1 type clay minerals can serve as an enormous and renewable pool of K supply in soil. The K releasing capacity of these minerals is governed by different agents like ionic strength, temperature and pH. Therefore, the release K from dioctahedral (Muscovite) and trioctahedral (Biotite) pure minerals were investigated at 25±1°C in batch reactors over the pH range of 8 to 12. The experiments performed until the steady state was achieved. At the start of each experiment, the high output solutions concentrations of Fe, Si, K and Al were recorded, after that a gradual reduction was observed leading to the establishment of steady state conditions. The release of Kwas more from the dissolution of biotite thanmuscovite dissolution.